(untitled) (Research, Society and Development, 2021)
Introduction: Obesity and depression are clinical entities whose etiology is a combination of genetic, biological, environmental and psychological factors capable of compromising quality of life. Objective: To evaluate the prevalence of depression before and after bariatric surgery and identify the sociodemographic and clinical characteristics. Methodology: cross-sectional, retrospective, survey-type study conducted in the period 2020-2021. The sample was composed of 5,160 individuals from various regions of Brazil who had undergone bariatric surgery. An online Google Forms questionnaire was used. Results: Of the 5,160 participants, 3199 (62%) did not have and did not develop depression after surgery; 305 (5.9%) had depression and remained after the intervention; 1192 (23.1%) had depression and improved post-surgery and 464 (9%) had no depression developed after surgery. The average age was 37-38 years. It was predominant: female gender, white skin color, complete high school and married individuals. The southeastern region was the most prevalent (p<0.001), as was alcoholism before and after surgery. Physical activity reduced the number of cases of depression after the procedure. Psychological follow-up was performed in 60% of the sample before surgery. The realization time of bariatric surgery was 18-60 months, and the gastric bypass technique was most prevalent. The prevalence of other psychiatric disorders was common among those with a history of depression. Conclusion: Depression was prevalent before and after the surgical intervention, however, bariatric surgery allowed the improvement of depressive disorder among those who already presented the pathology before the procedure.